Arterial branching and basal ganglia lacunes: A study in pure small vessel disease. (September 2017) - Moreton, Fiona C; Düring, Marco; Phan, Thanh; Srikanth, Velandai; Beare, Richard; Huang, Xuya; Jouvent, Eric; Chabriat, Hugues; Dichgans, Martin; Muir, Keith W
Introduction: Lacunes are defined morphologically by size and location, but radiological characteristics alone may be unable to distinguish small vessel disease aetiology from alternative mechanisms. We investigated the branching order of arterial vessels associated with basal ganglia lacunes in cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), in order to improve the understanding of their pathogenesis in pure cerebral small vessel disease. Patients and methods: Adults with a confirmed diagnosis of CADASIL were included. A pilot study was conducted in a Scottish CADASIL cohort. The Paris–Munich CADASIL cohort was used for independent validation. Lacunes identified on T1-weighted magnetic resonance imaging scans were registered to a standard brain template. A microangiographic template of the basal ganglia vasculature was automatically overlaid onto coronal slices, and raters estimated the vessel branching order related to each lacune. Results: Of 179 lacunes, 150 (84%) were associated with third-order vessels. In 14 incident lacunes, 11 (79%) were associated with third-order vessels. In the pilot study, lacune volume was significantly lower in lacunes associated with third-order vessels (0.04 ml ± 0.04 ml) compared to second-order vessels (0.48 ± 0.16 ml; p  < 0.001). Discussion: In this study of CADASIL patients, most lacunes were small and associated with third-order vessel disease. This suggests that these are the vessels primarily affected in cerebral small vessel disease. Microangiographic template techniques could be used to further investigate in a general stroke population whether finding large lacunes originating from higher order vessels indicates an alternative cause of stroke. Conclusion: Lacunes in pure small vessel disease are associated with the smallest vessels in the basal ganglia.